Ingestion of honey improves the symptoms of allergic rhinitis: Evidence from a randomized placebo-controlled trial in the East Coast of Peninsular Malaysia - Asha'ari, Zamzil Amin; Ahmad, Mohd Zaki; Wan Din, Wan Shah Jihan; Che Hussin, Che Maraina; Leman, Wan Ishlah (King Faisal Specialist Hospital and Research Centre, Riyadh, Saudi Arabia, 2013)
BACKGROUND AND OBJECTIVES: The role of honey in the treatment of allergic rhinitis (AR) is controversial. We studied the complementary effect of ingestion of a high dose of honey, in addition to standard medications, on AR. DESIGN AND SETTINGS: Prospective randomized placebo-controlled study. Subjects were recruited from an otolaryngology clinic in 2 tertiary referral centers in the East coast of Peninsular Malaysia. The study period ranged from April 2010-April 2011. METHODS: Forty AR patients were divided equally into a case group and a control group. All the subjects received a daily dose of 10 mg of loratadine for 4 weeks. The case group ingested 1 g/kg body weight of honey daily in separate doses for the 4-week period. The control group ingested the same dose of honey-flavored corn syrup as placebo. AR symptoms were scored at the start, week 4, and week 8 of the study. RESULTS: There were no significant differences between the mean total symptom score of the case and the control groups at the start of the study. At week 4, both groups showed progressive improvement in the symptoms; at week 8, only the case group showed a continuous improvement in the symptom score. Only the group that ingested honey showed a significant improvement in individual AR symptoms. The improvement persisted for a month after the cessation of the treatment. CONCLUSION: Honey ingestion at a high dose improves the overall and individual symptoms of AR, and it could serve as a complementary therapy for AR.